Effects of Sideritis scardica Extract on Glucose Tolerance, Triglyceride Levels and Markers of Oxidative Stress in Ovariectomized Rats - Jeremic, Ivica; Petricevic, Sasa; Tadic, Vanja; Petrovic, Dragana; Tosic, Jelena; Stanojevic, Zeljka; Petronijevic, Milan; Vidicevic, Sasenka; Trajkovic, Vladimir; Isakovic, Aleksandra (Planta Medica, 2019)
Menopause is characterized by deep metabolic disturbances, including decreased insulin sensitivity, adiposity, and changes in lipid profiles. Estrogen replacement therapy can partially reverse these changes, and while it is safe in most healthy postmenopausal women, there are still existing concerns regarding an increased risk for breast and endometrial cancer as well as a risk for cardiovascular and thromboembolic disease. Therefore, certain natural compounds with positive metabolic effects may be considered as a possible alternative or adjunctive treatment in patients not willing to take estrogens or patients with contraindications for estrogens. The aim of this study was to investigate the influence of Sideritis scardica (mountain tea) extract on metabolic disturbances induced by ovariectomy in rats. The study included 24 rats divided into three groups: ovariectomized rats treated with 200 mg/kg S. scardica extract for 24 weeks (n = 8), ovariectomized non-treated (n = 8), and Sham-operated (n = 8) rats. Food intake, weight gain, body composition, fasting glucose levels, response to oral glucose challenge, liver glycogen content, catalase activity, thiol groups, and malondialdehyde concentrations as well as AMP-activated protein kinase activity in liver cells were studied. Ovariectomized rats treated with S. scardica extract had lower blood triglycerides, reduced fasting glucose levels, as well lower glucose peaks after oral glucose challenge, increased liver glycogen content, and significantly higher catalase activity and thiol group concentration than non-treated ovariectomized rats. The ability of S. scardica extract to attenuate metabolic disturbances associated with ovariectomy was associated with the activation of AMP-activated protein kinase in liver cells.
Keywords: Sideritis scardica; Lamiaceae; menopause; ovariectomy; metabolic disturbance; AMPK